Waiting game: Beijing holds out for WAP, but customers aren't biting. - Holland, Lorien; Lawrence, Susan V. (Far Eastern Economic Review, 2000)
The Chinese government ordered a frantic roll-out of mobile phones that are wireless application protocol (WAP) enabled. WAP allows mobile-phone users with a suitable handset to access a pared-down, text-only version of the Internet through special WAP sites. China should be the perfect place for Internet access through mobile phone: For every four Chinese with a handset, there is only one with Internet access through a computer. Chinese officials therefore promoted powerful visions of a China transformed into the world's biggest Internet market through a computerless IT revolution. However, as is the case with many grand plans in China, a mass market in wireless Internet is a lot more difficult to pull off than it looks. Customers are not taking up WAP, and China's mobile-Internet revolution has yet to get far off the ground, despite the fact that mobile operators got the service going in March 2000, well ahead of government schedule. As a result of this lack of success, combined with a worldwide squeeze on funding for Internet plays, WAP is struggling in China.